Government assisted programs and unemployment reduction in developing economies: A study of Nigeria and Ghana - Edwin Agwu (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
This paper sets out to comparatively analyze various programs developed by the governments of Nigeria and Ghana towards alleviating unemployment. The inadequacies which have bedeviled these government assisted programs and their consequent failures warrant a review and reconsideration. The research employed qualitative case method with interviews as tools for data collection. Findings revealed a plethora of evidential facts with respect to perception of entrepreneurship in these countries which hinged on challenges such as inadequate funding, lack of requisite trainings, dearth of entrepreneurship education as well as the enabling environments. Most obvious among these challenges are the complete lack of governmental supports for the programs they propagated leading to the failure of various employment alleviation programs. This paper recommends the enactment of clear-cut policies by the governments under the leadership of a specialized ministry (ministry for entrepreneurship). Furthermore, a review and inclusion of entrepreneurship in the academic curriculum at all levels of the educational system will endear students to entrepreneurship studies. Finally, a holistic support of the organized private sectors in achieving a quantifiable target of full-fledged entrepreneurs within a decade will assist in unemployment reduction.
Keywords: F43; H53; J64; 330; Entrepreneurship; government assisted programs; unemployment reduction; business growth; Nigeria; Ghana